ITGAM coding variant (rs1143679) influences the risk of renal disease, discoid rash and immunological manifestations in patients with systemic lupus erythematosus with European ancestry. Issue 7 (25th November 2009) - Kim-Howard, Xana; Maiti, Amit K; Anaya, Juan-Manuel; Bruner, Gail R; Brown, Elizabeth; Merrill, Joan T; Edberg, Jeffrey C; Petri, Michelle A; Reveille, John D; Ramsey-Goldman, Rosalind; Alarcon, Graciela S; Vyse, Timothy J; et al.
Abstract : Purpose: It was hypothesised that the coding variant (R77H), rs1143679, within ITGAM could predict specific clinical manifestations associated with systemic lupus erythematosus (SLE). Method: To assess genetic association, 2366 patients with SLE and 2931 unaffected controls with European ancestry were analysed. The patients with SLE were coded by the presence or absence of individual American College of Rheumatology criteria. Logistic regression and Pearson χ 2 tests were used to assess statistical significance. Results: For overall case-control analysis, a highly significant association was detected (p=2.22×10−21, OR 1.73). Using case-only analysis, a significant association was detected with renal criteria (p=0.0003), discoid rash (p=0.02) and immunological criteria (p=0.04). When patients with SLE were compared with healthy controls, the association became stronger for renal (p=4.69×10−22, OR 2.15), discoid (p=1.77×10−14, OR 2.03) and immunological (p=3.49×10−22, OR 1.86) criteria. Risk allele frequency increased from 10.6% (controls) to 17.0% (SLE), 20.4% (renal), 18.1% (immunological) and 19.5% (discoid). Conclusion: These results show a strong association between the risk allele (A) at rs1143679 and renal disease, discoid rash and immunological manifestations of SLE.